Mutant isocitrate dehydrogenase 1 inhibitor ivosidenib in combination with azacitidine for newly diagnosed acute myeloid leukemia - DiNardo, CD; Stein, AS; Stein, EM; Fathi, AT; Frankfurt, O; Schuh, AC; Döhner, H; Martinelli, G; Patel, PA; Raffoux, E; Tan, P; Zeidan, AM; et al. (American Society of Clinical Oncology, 2020)
PURPOSE: Ivosidenib is an oral inhibitor of the mutant isocitrate dehydrogenase 1 (IDH1) enzyme, approved for treatment of IDH1-mutant (mIDH1) acute myeloid leukemia (AML). Preclinical work suggested that addition of azacitidine to ivosidenib enhances mIDH1 inhibition–related differentiation and apoptosis.